EFFECT OF ETHYLENE COMPOUNDS ON BANANA RIPENING AND POST-HARVEST PACKAGING (STORAGE) OF CITRUS FRUITS - Sutrisno Adi Prayitno (Agroindustrial Technology Journal, 2023)
Ethylene compounds are used in the post-harvest handling of horticultural products to speed up the ripening process. Suitable storage and packaging would maintain the quality of horticultural products. Horticultural products undergo further metabolism even after harvesting such as transpiration, respiration, maturation, and ripening. To prevent the rapid deterioration of horticultural produce (physical, nutritional, and sensory), postharvest handling requires proper ethylene dosing, proper packaging, and storage of the product during handling. The aim of this research was to observe and find out the effect of the ripening stage on bananas and how to package orange fruits on changes in quality (physical and sensory) during post-harvest storage. The results showed that there was an influence of ethylene compounds on the ripening process of bananas on sensory characteristics, the color changed from yellow to blackish brown, the aroma became more fragrant and the sweet taste became sweet and sour; increasing the value of total suspended solids (TSS) and decreasing the weight of bananas. Plastic packaging equipped with perforated holes also affects the quality of oranges, lower orange fruit weight loss, and better sensory characteristics in texture and color compared to oranges packaged in plastic without holes. Hence, the storage of oranges fruits in air-tight conditions is not recommended due to it can make CO2 to be trapped and accumulate in the packaging which can result in the formation of water droplets or dew that affect the quality of orange fruits.